Rapid generation and characterization of recombinant HCoV-OC43-VR1558 infectious clones expressing reporter Renilla luciferase - Fei Ye; Na Wang; Qiongge Guan; Mengwei Wang; Jiewei Sun; Desheng Zhai; Baoying Huang; Ying Zhao; Wenjie Tan (Biosafety and Health, 2024)
Viral infectious clones (ICs) serve as robust platforms for studying viral biology and screening antiviral agents using reverse genetics. However, the molecular profiles and complex limitations of human coronaviruses (HCoVs) pose a challenge to ICs development. In this study, we report a novel platform to develop the ICs for HCoV-OC43-VR1558 using a one-step assembly method in yeast by transformation-associated recombination (TAR) technology. Recombinant HCoV-OC43-VR1558, named as rOC43(1558)-WT, was rapidly generated by TAR. In addition, recombinant HCoV-OC43-VR1558-expressing reporter genes, named as rOC43(1558)-ns2FusionRluc, was also generated based on TAR by inserting the ns2 region of the IC with Renilla luciferase (Rluc). We further characterized their replication through virus titration using 50 % tissue culture infective dose (TCID50) and indirect immunofluorescence assay (IFA), luciferase reporter assay, and western blotting (WB) assay. The genetic stability of the recombinant HCoV-OC43 was assessed through viral genome sequencing following passaging in BHK-21 cells. These reporter viruses were validated as screening tools for inhibitors in vitro by evaluating the antiviral activities of remdesivir and chloroquine. The phenotypes of HCoV-OC43-VR1558 and HCoV-OC43-VR759 were compared in vitro and in vivo. The TAR-based one-step assembly of IC was successfully applied, facilitating the rapid generation of recombinant HCoV-OC43 and providing a useful platform for the investigation of biological mechanisms, development of vaccines and diagnostic tests, and screening inhibitors of HCoVs.